Current status of the recycling of e-waste in Indonesia. Issue 3 (4th July 2022) - Kurniawan, Kurniawan; Soefihara, Muhammad Dzikri Ahira; Nababan, Deddy Chandra; Kim, Sookyung
ABSTRACT: Electronic waste (e-waste) has become a major economic and environmental concern. It requires the development of sustainable and integrated recycling systems capable of recovering valuable constituents while simultaneously protecting the environment. While many developed countries have established such recycling systems, most developing countries, including Indonesia, lack such systems and have a low level of public awareness about e-waste. This article focuses on the current state of e-waste recycling in Indonesia. The estimated amount of e-waste generation and distribution in the country, potential economic recovery, relevant legal frameworks, and recycling practices are presented. The review also highlights barriers to formal e-waste management and recycling in Indonesia, such as (i) superiority of the informal sector, (ii) lack of regulation and infrastructure, (iii) lack of awareness and reliable data about e-waste, (iv) low rate of research works on recycling technology development, and (v) large diversity of socio-economic and geographic conditions in Indonesia. The study suggests strategies for establishing a sustainable e-waste recycling system in Indonesia, including potential processing routes and scenarios that integrate the actors involved in e-waste collection, pretreatment, and metal extraction.